WOMEN’S CLOTHING PRACTICE DURING THE XX CENTURY IN NOVI PAZAR AND ENVIRONMENT - Aksić, Nina; Zilјkić Hasna (Bulletin of the Institute of Ethnography SASA, 2022)
In this paper we will present everyday clothing in the city and village, during the XX century, on the ground of Novi Pazar. The emphasis is placed on the women`s everyday clothing and special features that are reflected primarily in confessional practices. In addition to the differences in clothing that arose from the confessional practices, we will point out to the others aspects which influenced on the diversity of clothing, such as – education, employment, the influence of the external environment (people outside the family, the media and etc.), economic status etc. Differences conditioned by the status of women in society, which changed significantly after World War II, with greater emancipation of women and their gradual exit from the patriarchal family framework caused changes in clothing appearance. The aim of this paper is to present the complexity of everyday clothing practices of women and its changes in the territory of Novi Pazar and its environment.